PENGANGGARAN BERBASIS KINERJA DAN AKUNTABILITAS KINERJA PADA LEMBAGA PEMERINTAH - Lukito, Daniel; Qadaar, Amiruddin; Mardikawati, Budi; Susanti, Melly (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
The aim of this research is to investigate the relationship between performance-based budgeting and performance accountability of government institutions. Government performance accountability is measured by indicators of program smoothness, budget implementation, performance indicators, financial analysis, evaluation reporting, and program duration. Performance-based budgeting uses measures of accountability and transparency, budget fairness, efficiency, and effectiveness as independent variables. Decisions are made by individuals who have power in the best interests. This research involved 39 department employees, secretaries, section heads, sub-division heads, and work subunits from the Regional Work Unit (SKPD) of the Environment and Forestry Service of Bengkulu Province who helped prepare the government budget. Data was collected through a questionnaire method, and respondents were given one. To analyze the data, the Spearman Rank test and hypothesis testing were used. The results of this research show that the three independent variables-implementation of performance-based budgeting with metrics of budget accountability and transparency, budget discipline, budget fairness, budget efficiency, and budget effectiveness-influence the performance accountability of government institutions